Response of five eco-physiological parameters, to the application of potassium in sunflower (Asteraceae), under semi-arid climate - Díaz-López, Ernesto (2020)
In order to know the effect of three levels of potassium on five eco-physiological parameters in sunflower, open-pollinated achenes Victory cultivar, were sown at a density of 11.08 plants m-2 with a fertilization of 100N-50P kg ha-1 N=nitrogen, P= phosphorous, K= potassium. Traits evaluated were: agronomic yield, leaf area index, light attenuation coefficient and intercepted radiation. The treatments consisted of three potassium levels: 0, 50 and 100 kg ha-1 (K2O) and four repetitions (3x4) resulting in 12 experimental units, which were evaluated under a randomized complete block design. The results indicate that the application of 50 and 100 kg ha-1 of potassium increase the agronomic yield, leaf area index, intercepted radiation as well as the light attenuation coefficient. From this investigation it can be concluded, that potassium is a very important nutrient for sunflower when it is sown in dry climates such as the Tehuacan valley, Puebla.